Commercial Providence: The Secret Destiny of the American Empire - Mendis, Patrick (Hamilton Books, 2012)
What is behind the success of America? Does America manifest its destiny by other means? Author Patrick Mendis explores unseen forces that have guided America to global dominance. He details how the creation of Madison's 'Universal Empire' through Hamilton's 'Federalism' realizes Jefferson's 'Empire of Liberty.' The author then unveils America's Masonic endgame of universal brotherhood: E Pluribus Unum.